Adsorption and recovery issues of recombinant monoclonal antibodies in reversed‐phase liquid chromatography†. Issue 1 (9th December 2014) - Fekete, Szabolcs; Beck, Alain; Wagner, Elsa; Vuignier, Karine; Guillarme, Davy
<x xml:space="preserve">Abstract</x> The poor recovery of large biomolecules is a well‐known issue in reversed‐phase liquid chromatography. Several papers have reported this problem, but the reasons behind this behavior are not yet fully understood. In the present study, state‐of‐the‐art reversed‐phase wide‐pore stationary phases were used to evaluate the adsorption of therapeutic monoclonal antibodies. These biomolecules possess molar mass of approximately 150 000 g/mol and isoelectric points between 6.6 and 9.3. Two types of stationary phases were tested, the Phenomenex Aeris Widepore (silica based), with 3.6 μm superficially porous particles, and the Waters Acquity BEH300 (ethylene‐bridged hybrid), with 1.7 μm fully porous particles. A systematic investigation was carried out using 11 immunoglobulin G1, G2, and G4 antibodies, namely, panitumumab, natalizumab, cetuximab, bevacizumab, trastuzumab, rituximab, palivizumab, belimumab, adalimumab, denosumab, and ofatumumab. All are approved by the Food and Drug Administration and the European Medicines Agency in various therapeutic indications and are considered as reference antibodies. Several test proteins, such as human serum albumin, transferrin, apoferritin, ovalbumin, and others, possessing a molar mass between 42 000 and 443 000 g/mol were also evaluated to draw reliable conclusions. The purpose of this study was to find a correlation between the adsorption of monoclonal antibodies and their physicochemical properties. Therefore, the impact of isoelectric point, molar mass, protein glycosylation, and hydrophobicity was investigated. The adsorption of intact antibodies on the stationary phase was significantly higher than that of proteins of similar size, isoelectric point, or hydrophobicity. The present study also demonstrates the unique behavior of monoclonal antibodies, contributing some unwanted and unpredictable strong secondary interactions.